MCM-41-Accelerated PWA Catalysis of Friedel-Crafts Reaction of Indoles and Isatins - Liuzhuang Xing; YongHai Hui; Jinghui Yang; Xuejian Xing; Yadong Hou; Yang Wu; Kui Fan; Wei Wang (Journal of Chemistry)
Ordered mesoporous siliceous material has been identified as one of the key elements of the catalysis concept. Here we report an efficient Friedel-Crafts reaction of indoles with isatins catalyzed by PWA/MCM-41, which got the di(indolyl)indolin-2-ones derivatives with high yield. Moreover, the catalysts were characterized by XRD and SEM/EDS, the EDS spectrum indicated that the catalyst used in this reaction also contains tungsten, and the proposed mechanism for the synthesis of 3,3-di(indolyl)indolin-2-ones was also discussed. Finally, the catalyst can be reused repeatedly for several times without obvious loss of activity.